PENATAAN FASILITAS INTEGRASI ANTARMODA DI STASIUN SUKABUMI - Sri Yuniarti; Deni Nurdiansyah; Sri Widayatie (FTSP Universitas Jayabaya, 2019)
Sukabumi Station is a Railway Station located in the center of Sukabumi City and it is alternative choice for people who will travel outside the city. The current condition of Sukabumi Station does not have integration facility that supports passengers to transfers easily. Reflect on that problem above, it is important to analyze pedestrian facilities and parking analysis to improve accessibility from and to Sukabumi Station. Based on the result of the analysis calculation, if can be concluded that the width of the sidewalk of 1.6 meters, where the initial condition of the sidewalk width is only 1.2 meters, so the sidewalk width must be widened. The recomended parking space for motorcycle is 61 parking space unit (PSU), slightly improved from the old condition which could 41 PSU load only. While for car, the parking space facing no problem since the parking space allows to 19 PSU where the current needs just 15 PSU. Therefore it is necessary to adjust the parking space capacity so it can meet the ideal condition. As an addition, the recomendation angle used in parking for car are 90° dan 60°.